2024
DOI: 10.3390/metabo14020122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Astragaloside IV on Hearing, Inflammatory Factors, and Intestinal Flora in Mice Exposed to Noise

Junyi Li,
Jian Yang,
Yun Xia
et al.

Abstract: Long-term exposure to noise can cause irreversible hearing loss. Considering that there is no effective drug treatment, it is important to seek preventive treatment for noise-induced hearing loss (NIHL). Although astragaloside IV (AS-IV) protects against NIHL by reducing serum inflammatory factors, there is scarce information on the regulation of inflammatory factors by AS-IV to prevent NIHL. We investigated the hearing thresholds and relationship between the serum levels of inflammatory cytokines and intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The gut microbiota is recognized to have an essential role in the development of metabolic diseases such as hyperlipidemia, diabetes, and obesity [26][27][28][29]. Multiple studies have demonstrated that polyphenols could effectively regulate the gut microbiota [30,31].…”
Section: Effects Of Fepe On Gut Microbiota In Micementioning
confidence: 99%
“…The gut microbiota is recognized to have an essential role in the development of metabolic diseases such as hyperlipidemia, diabetes, and obesity [26][27][28][29]. Multiple studies have demonstrated that polyphenols could effectively regulate the gut microbiota [30,31].…”
Section: Effects Of Fepe On Gut Microbiota In Micementioning
confidence: 99%